2008
DOI: 10.1017/s1074070800027966
|View full text |Cite
|
Sign up to set email alerts
|

Economic Determinants of Invasion and Discovery of Nonindigenous Insects

Abstract: Introductions of nonindigenous organisms into the United States have been linked to international trade. The individual contributions of imports, immigration, and international travel, however, are poorly understood because introduction dates are unavailable. We examine relationships between economic trends and discoveries of nonindegenous insects and use these relationships to infer the timing and determinants of introductions. We find that a few variables can explain much variation in species introductions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For instance, in a global analysis across taxa, Westphal et al (2008) concluded that a country's level of international trade (i.e., its amount of merchandise imports) is the best predictor of the number of alien invasive species found within its borders. Similarly, Hlasny and Livingston (2008) suggested that agricultural import levels are the best predictor of the number of introduced insect species in the US. However, to implement finer-scale prediction of potential entries of invasive organisms requires more detailed knowledge about the quantity, origins, and destinations of various types of imports (Hulme 2009;Hulme et al 2008;Kenis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a global analysis across taxa, Westphal et al (2008) concluded that a country's level of international trade (i.e., its amount of merchandise imports) is the best predictor of the number of alien invasive species found within its borders. Similarly, Hlasny and Livingston (2008) suggested that agricultural import levels are the best predictor of the number of introduced insect species in the US. However, to implement finer-scale prediction of potential entries of invasive organisms requires more detailed knowledge about the quantity, origins, and destinations of various types of imports (Hulme 2009;Hulme et al 2008;Kenis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To control for the arrival of infested goods in the United States, we use agricultural imports, merchandise imports and all imports, as alternative measures. We expect agricultural imports to be an important determinant of species introductions, because of the a priori high rate of infestation and nonsterile conditions of agricultural shipments, and because of evidence in prior literature (Work et al 2005, Hlasny andLivingston 2008). Merchandise imports and imports at large are thought to contribute less to species introductions, because they include commodities that are less likely to be infested.…”
Section: Methodsmentioning
confidence: 99%
“…There is a great deal of circumstantial evidence suggesting a causal relationship between humanrelated activities and introductions of invasive organisms (Kim andWheeler 1991, NRC 2002). The existing literature blames in particular the trade in animals and plants, raw materials, and horticultural products, and other merchandise (Hlasny and Livingston 2008, and references therein). Although quarantine and inspection systems attempt to reduce biological risks from imports, improper movement of commodities susceptible to infestation remains a signiÞcant problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that a country's level of international imports (Levine and D'Antonio 2003;Westphal et al 2008)-either in total or specifically within the agricultural sector (Hlasny and Livingston 2008)-is a reasonable predictor of the number of alien species that can be expected to be introduced. However, while gross trade volumes may serve as a good proxy for estimating the anticipated number of new invasions in a region of interest, determining the finer-scale geographic distribution of these new entries requires detailed knowledge on the movement of specific commodities (i.e., potential carriers of invasive species) through the region's network of freight shipment corridors (Hulme et al 2008;Hulme 2009;Kenis et al 2009).…”
Section: Introductionmentioning
confidence: 99%